Pelatihan Penggunaan Modul Kesehatan Reproduksi Remaja bagi Guru di SMP Muhammadiyah 4 Kabupaten Bandung: Training on the Use of Adolescent Reproductive Health Module for Teachers in SMP Muhammadiyah 4, Bandung Regency - Nurhayati, Nurhayati; Kamila, Ami; Rinjani, Vanisa Maulina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Adolescent reproductive health education in schools is essential to provide alternative solutions to overcome student reproductive health problems. This fact makes teachers a more appropriate choice for understanding reproductive health in adolescents. Teachers have not been able to provide reproductive health education according to the needs of students, so in implementing reproductive health education in schools, teachers must prepare knowledge and skills in conveying material to facilitate the learning process of their students properly. Teachers need to receive training to be able to provide students with a proper understanding of reproductive health. A module is a tool for absorbing student knowledge; by understanding the adolescent reproductive health module, the teacher will be able to convey the material expected by students. The aim is to provide "training on the use of Adolescent Reproductive Health Modules for Teachers at SMP Muhammadiyah 4 Bandung" Regency to increase teachers' knowledge regarding adolescent reproductive health. The results indicate that there is an increase in the knowledge of teachers. The average pre-test result of participants was 84% with a standard deviation of ±0.905, and the average post-test result was 88.18% with a standard deviation of ±1.206. So it can be concluded that there is an increase of 5% from the pre-test and post-test results after training teachers. This community service activity certainly increases knowledge, understanding, and ability to detect early problems of teenagers in their schools.